Exploring EFL learners attitudes toward the application of a model of writing e-portfolio - Azarfam, Aliasghar Yousefi; Abd. Samad, Arshad; Noordin, Nooreen (Australian International Academic Centre, 2016)
This study aimed to explore the attitudes of two groups of EFL learners toward the application of a model of writing e-portfolio in developing their writing skill. It was a follow-up study to an experiment on the effectiveness of this model on the writing performance of Iranian EFL learners. One group had used certain strategies based on the analytic traits of writing, while the other group had not used such strategies in the writing process. Four class members from each writing e-portfolio group were selected purposively for conducting the semi-structured interviews in this research. The findings showed that members of the group that used strategies based on analytic traits of writing had acquired a sort of awareness towards the different qualities of writing, claiming that knowing about the analytic traits of writing caused them to understand the necessity of paying attention to all aspects of writing and not just the usage and mechanical correctness of it. They referred to the role of Peer Checklist in reminding them of the writing qualities to be considered in their self- and peer-assessment. The results of the learners’ feedback in both e-portfolio groups further revealed that the electronic environment of e-portfolios can play a significant role in facilitating the writing task performance of the learners and consequently improving their writing skill in both e-portfolio groups. On the whole, the student self-reports indicated that the use of strategies based on analytical traits was able to heighten awareness regarding important aspects of writing.